Basics of Flow Microreactor Synthesis - Yoshida, Jun-ichi (Springer, 2015)
This book provides in a concise form the principles and applications of flow microreactors in organic and polymer synthesis. Recently, it became possible to conduct chemical reactions in a flow reactor in laboratory synthesis. The flow microreactor enables reactions that cannot be done in batch, opening a new possibility of chemical synthesis. Extremely fast mass and heat transfer and high-resolution residence time control are responsible for the remarkable features of that process. The book is not an exhaustive compilation of all known examples of flow microreactor synthesis. Rather, it is a sampling of sufficient variety to illustrate the concept, the scope, and the current state of flow microreactor synthesis. Researchers both in academia and in industry will be interested in this book because the topics encompassed by the book are vigorously studied in many university and company laboratories today.